ParC and GyrA May Be Interchangeable Initial Targets of Some Fluoroquinolones in Streptococcus pneumoniae - Varon, Emmanuelle (American Society for Microbiology, 1999)
To evaluate the role of known topoisomerase IV and gyrase mutations in the fluoroquinolone (FQ) resistance of Streptococcus pneumoniae, we transformed susceptible strain R6 with PCR-generated fragments encompassing the quinolone resistance-determining regions (QRDRs) of parC or gyrA from different recently characterized FQ-resistant mutants. Considering the MICs of FQs and the GyrA and/or ParC mutations of the individual transformants, we found three levels of resistance. The first level was obtained when a single target, ParC or GyrA, depending on the FQ, was modified. An additional mutation(s) in a second target, GyrA or ParC, led to the second level. The highest increases in resistance levels were seen for Bay y3118 and moxifloxacin with the transformant harboring a double mutation in both ParC and GyrA. When a single modified target was considered, only the ParC mutation(s) led to an increase in the MICs of pefloxacin and trovafloxacin. In contrast, the GyrA or ParC mutation(s) could lead to increases in the MICs of ciprofloxacin, sparfloxacin, grepafloxacin, Bay y3118, and moxifloxacin. These results suggest that the preferential target of trovafloxacin and pefloxacin is ParC, whereas either ParC or GyrA may both be initial targets for the remaining FQs tested. The contribution of the ParC and GyrA mutations to efflux-mediated FQ resistance was also examined. Active efflux was responsible for two- to fourfold increases in the MICs of ciprofloxacin for the transformants, regardless of the initial FQ resistance levels of the recipients.